Decentralization and Macroeconomic Management - Ter-Minassian, Teresa (IMF Working Papers; Working Paper, 1997)
The literature on fiscal federalism has amply discussed both the potential efficiency and welfare gains from decentralization and the potential trade-offs between decentralization and income redistribution. By contrast, it has generally put less emphasis on the effects of decentralization on macroeconomic management, although policymakers worldwide increasingly have to grapple with these effects. This paper examines the constraints that a high degree of decentralization can place on the ability of the central government to carry out its traditional macroeconomic management functions and explores various ways to minimize these constraints.